Precipitation Behavior of Nitride Inclusions in K418 Alloy under the Continuous Unidirectional Solidification Process - Guo, Xiliang; Deng, Kang; Yu, Jianbo; Li, Qiang; Zhao, Wencheng; Yang, Fan; Li, Xia; Ren, Zhongming; Hou, Yuan; Zhong, Yunbo (ISIJ International, 2021)
Adopting effective routs to control the precipitation and size of nitride inclusions in superalloys during the solidification is a very interesting subject for metallurgists. The precipitation behavior of nitride inclusions in K418 alloy under the continuous unidirectional solidification process was investigated by scanning electron microscopy, ASPEX Explorer, and LECO ONH-836. The results show that there were two types of nitride inclusions in the K418 alloy ingot: TiN and complex inclusion of Al2O3–TiN. There were gradient distributions of the number density, average and max sizes of nitride inclusions along the casting direction, as well as the contents of Ti and N. Based on the thermodynamic and kinetic calculations, the precipitation time of TiN inclusion changed from mushy to liquid zones under different initial contents of Ti and N. Al2O3 inclusion began to precipitate in liquid zone and acted as the nucleation site for TiN inclusion. The radius of TiN inclusion increased from 3.2 µm at 0.36 K/s to 8.6 µm at 0.08 K/s when the fraction of solid approached 1. The nitride inclusions can be refined and reduced in the K418 alloy ingot under the continuous unidirectional solidification process compared with those in revert K418 alloy. The methods to control the precipitation and size of nitride inclusions were reducing the contents of N and O and increasing the cooling rates.